State-of-the-art review on cold-formed steel channel sections under compression - Ananthi, G. Beulah Gnana (Journal of Structural Engineering, 2024)
This paper presents a detailed review on cold-formed steel channel sections, which are subjected to both axial and eccentric compressive forces. Different cross-sections with single and built-up configurations are presented in this paper. Literature pertaining to experimental, theoretical and numerical investigations are reviewed in detail. The main objective of this literature survey is to study the available literature and to propose the required research work for the development of various other single and compound cold-formed steel sections. Research in cold-formed steel channel sections subjected to compressive forces shows the importance of channel sections and compares with other possible sections.